Matching between the Employment of Sultan Qaboos University’s Graduates in the Labor Market and their Academic Specialties - Salim Al Ghnboosi, Salim (Jordan Journal of Educational Sciences, 2014)
The aim of this study was to determine the positions compatibility of graduates at Sultan Qaboos University with their academic specialization. The data were collected from 7718 male and female graduates; 5714 cases were valid for analysis, these represented 74% of the total. The independent variables were: gender, college, specialization, job, the employer, and year of graduation. The results revealed that the percentage of compatibility between the academic specialization of graduates and their positions after graduation was 84.1%, whereas incompatibility was 15.9%. Based on gender, the male employment percentage was 48.8% whereas females’ was 51.2%. In addition, 89.1% of the graduates work at the government sector, while 10.9% in the private sector, where female was 74.9% in public sector, while was 25.1% at the private sector. Upon the results, the study recommended studies to ensure that future labor market needs and skills are met and further studies were suggested, and the period that graduates keep on as jobs seekers